Metal Forming Practise Processes - Machines - Tools - Tschätsch, Heinz (Springer Berlin Heidelberg : Imprint: Springer, 2006)
Economical and flexible, advanced metal-forming processes form the core of modern industrial production. This professional sourcebook presents the most important metal-working and shearing processes and the related machines and tooling - in a concise form that is supplemented by ample illustrations, tables and flow charts. Practical examples show how to calculate the forces and strain energy of the processes and the specific parameters of the machines, while exercises enable readers to check their comprehension. Today's production units are automated as much as possible using modern CNC engineering to reduce time and costs, so the book introduces flexible manufacturing systems in metal forming and the handling systems required for automation. For engineers and managers on the shop floor, this book is intended as an easily-navigable reference work. Students can use this book for reference, saving them time making notes in the lecture theatre so that they can pay better attention to the lecture. Carefully translated from the eighth revised German-language edition, Metal Forming practise comprises a uniquely valuable learning reference tool for students, engineers and technicians.